An Experimental and Numerical Study of Landslides Triggered by Agricultural Irrigation in Northwestern China. (1st December 2020) - Gu, Tianfeng; Sun, Pingping; Wang, Jiading; Lin, Herry; Xu, Yuanjun; Kong, Jiaxu; Sun, Bin
Abstract : Chinese Loess Plateau (CLP) has become one of the high-incidence areas of landslide disasters in China, especially at the edge of the tablelands where irrigation has been practiced at a large scale since the 1960s. Heifangtai tableland, located in the CLP in Yongjing County, Gansu Province, has been selected as a case, where more than 90 slidings occurred in the past three decades. Field monitoring and laboratory tests were conducted to obtain the soil-water characteristic curve, unsaturated soil shear strength, irrigation water infiltration, and the groundwater level change. Based on these results, a three-dimensional numerical model of the slope was established, and the change of seepage field and slope stability before and after irrigation was investigated using simulations and compared with the observed data. The results show that flood irrigation raised the water table, and the increase of soil moisture in the flooded area was more significant than that in the nonirrigated area. The rising speed of the groundwater level was about 0.25 m/yr, with an amplitude of 0.5 m. Near the slope, the hydraulic gradient of the concave slope was steeper than the convex slope. The shear strength of the loess decreased with increasing soil moisture, and the tensile strength was about 15% of the cohesion. Numerical results showed that after three years of continuous flood irrigation at the back of the slope, the slope stability coefficient decreased by 0.12. After irrigation, the potential slip zone slightly expanded. The reason why landslides often occurred at the back of the gully or the landslide was that the water table was shallower on concave slopes and the soil moisture of the concave slopes was more susceptible to irrigation.